Gonzalo, Manuel. India from Latin America: Peripherisation, Statebuilding, and Demand-Led Growth. Taylor & Francis, 2023. 268 pp. - Guido Enrique Jaime Aschieri Hers (H-Industri@)
Reseña del libro India from Latin America: Peripherisation, Statebuilding, and Demand-Led Growth de Manuel Gonzalo